2014
DOI: 10.21556/edutec.2014.48.156
|View full text |Cite
|
Sign up to set email alerts
|

Percepción de los alumnos de Educación Primaria de la Universidad de Salamanca sobre su competencia digital

Abstract: Presentamos una investigación cuyo objetivo es el de conocer la percepción que tienen los alumnos de Educación Primaria de la Universidad de Salamanca sobre su competencia digital. Se ha seguido una metodología cuantitativa, un método no experimental y descriptivo, y se ha utilizado la técnica del cuestionario para la recogida de datos. La muestra está compuesta por un total de 52 alumnos de una población de 57. Los resultados obtenidos ponen de manifiesto que la mayoría de alumnos se sienten capacitados para … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 2 publications
1
5
0
9
Order By: Relevance
“…These results underline the importance of incorporating experiences in the classroom to improve this area of digital competence. The studies by Cabezas, Casillas, and Pinto [51], Cózar and Roblizo [21], Prendes, Castañeda, and Gutierrez [52], Romero, Hernández, and Ordoñez [53], Romero-Martín et al [25], Garzón Artacho et al [54], Pozo-Sánchez et al [15] and Napal Freire et al [26] found a low level of training of future teachers in use of digital educational resources. It is a very important area of digital competence for teachers, who need to know how to manage the use of ICT in the classroom and have skills for selecting, adapting, and creating teaching materials and for evaluation in digital settings [55].…”
Section: Discussionmentioning
confidence: 99%
“…These results underline the importance of incorporating experiences in the classroom to improve this area of digital competence. The studies by Cabezas, Casillas, and Pinto [51], Cózar and Roblizo [21], Prendes, Castañeda, and Gutierrez [52], Romero, Hernández, and Ordoñez [53], Romero-Martín et al [25], Garzón Artacho et al [54], Pozo-Sánchez et al [15] and Napal Freire et al [26] found a low level of training of future teachers in use of digital educational resources. It is a very important area of digital competence for teachers, who need to know how to manage the use of ICT in the classroom and have skills for selecting, adapting, and creating teaching materials and for evaluation in digital settings [55].…”
Section: Discussionmentioning
confidence: 99%
“…Es primordial aproximarse a las concepciones del profesorado en activo de las etapas pre-universitarias, ya que se considera clave para poder actuar convenientemente en las etapas formativas superiores (Arancibia y Badia, 2015;Cabezas, Casillas y Pinto, 2014). Sólo conociendo las prácticas actuales, descubriendo las opiniones del profesorado en activo e identificando la realidad de lo que acontece en el aula, se pueden establecer actuaciones concretas que sanen las carencias detectadas.…”
Section: Tic Mass-media Y Patrimonio Dentro De Los Recursos De Innovaciónunclassified
“…However, this apparent contradiction, in our opinion, is explained by the insecurity generated in those surveyed by the lack of specific training to work with these tools and the scarce digital skills they possess to do so (Cabero, 2014;Colomer et al, 2018;Girón et al, 2019). This has been evident in a variety of research studies that focus on the need to strengthen initial teacher training in this regard (Tascón, 2012;Trigueros et al, 2012;Cabezas et al, 2014;Cózar and Roblizo, 2014;Mur, 2016;Colomer et al, 2018;, so that ICT ceases to be an element of motivation or experimentation, and becomes the origin of real methodological change in the classroom (Marquès, 2013).…”
Section: Discussionmentioning
confidence: 95%